Territorial capital as a driver of regional competitiveness: A theoretical framework - Andrejević Panić Andrea; Cvetanović Slobodan (Spatium)
The paper analyzes contemporary theoretical approaches to explaining the elements of territorial capital, which are recognized as key drivers of improving regional competitiveness. Special emphasis is placed on the decomposition of territorial capital depending on ownership structure and materiality. The paper thoroughly examines the characteristics of the elements of territorial capital, with a particular focus on their contribution to the growth of regional competitiveness. The research is based on the application of descriptive economic analysis, enriched with visual representations that depict the concept of territorial capital and regional competitiveness. Descriptive analytical tools have enabled the precise description of the essential features of various components of territorial capital, while visual representations have further enhanced the understanding and interpretation of the core concepts investigated in the study. In the course of the research, classical and contemporary sources were utilized to analyze the nature and key determinants of endogenous growth, as well as the essence of the concepts of regional competitiveness and territorial capital. A specific methodological approach was directed towards the systematization and analysis of territorial capital categories, with typological research methods predominantly employed to achieve precise classification and interpretation of relevant components. The results of the research indicate that the improvement of regional competitiveness largely depends on the efficient and effective utilization of available territorial capital. The primary task of policymakers is to facilitate networking, cooperation, and coordination among entrepreneurial and other participants in developmental processes, with the goal of creating synergies that contribute to sustainable development and regional competitiveness.